Islanding detection method based on a Thevenin‐like model. Issue 13 (1st October 2015) - Di Fazio, Anna Rita; Fusco, Giuseppe; Russo, Mario
Abstract : Reliable detection of islanded operation is essential in distribution systems with large penetration of the distributed generation. Commonly‐used protections present performance limitations in terms of sensitivity and stability. To overcome such limitations, this study proposes to enrich classical protections by adding a passive islanding detector based on a new method. It adopts a linear representation of the low voltage distribution system, referred to as Thevenin‐like model. On the basis of the voltage and current measures at the detector installation point, two model parameters are estimated and are used to distinguish islanded from grid‐connected operation. The proposed detector presents high sensitivity and reliability, does not require expert tuning, can be installed in different points of the distribution system and is economically viable. Numerical analysis and simulations, evidence the effectiveness of the proposed method.